2013
DOI: 10.1016/j.laa.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Large free linear algebras of real and complex functions

Abstract: Let $X$ be a set of cardinality $\kappa$ such that $\kappa^\omega=\kappa$. We prove that the linear algebra $\mathbb{R}^X$ (or $\mathbb{C}^X$) contains a free linear algebra with $2^\kappa$ generators. Using this, we prove several algebrability results for spaces $\mathbb{C}^\mathbb{C}$ and $\mathbb{R}^\mathbb{R}$. In particular, we show that the set of all perfectly everywhere surjective functions $f:\mathbb{C}\to\mathbb{C}$ is strongly $2^\mathfrak{c}$-algebrable. We also show that the set of all functions $… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…The construction of the function from the assertion of Proposition 3.3 was presented for example in [9]. By Theorem 1.5 we can obtain the following result.…”
Section: Functions That Are Continuous On a Fixed G δ Setmentioning
confidence: 91%
See 1 more Smart Citation
“…The construction of the function from the assertion of Proposition 3.3 was presented for example in [9]. By Theorem 1.5 we can obtain the following result.…”
Section: Functions That Are Continuous On a Fixed G δ Setmentioning
confidence: 91%
“…Moreover, in [9], the authors obtained strong c-algebrability of C G , for some sets G and asked a question about strong c-algebrability of C R\Q . In this paper we fully answer for the question about strong c-algebrability of C G in the general case (i.e.…”
Section: Functions That Are Continuous On a Fixed G δ Setmentioning
confidence: 99%
“…Bartoszewicz, M. Bienias, and S. Głąb showed in [6,Theorem 8] that the family of nowhere continuous Darboux functions is 2 c -algebrable. This result was improved up to strongly 2 c -algebrability by A. Bartoszewicz, S. Głąb, and A. Paszkiewicz in [9,Theorem 3.3]. Hence D is strongly 2 c -algebrable.…”
Section: Definitionmentioning
confidence: 86%
“…Recall that the mentioned earlier nowhere continuous Darboux functions (which are contained in D \ (Q ∪Ś)) are strongly 2 c -algebrable [9,Theorem 3.3]. In the same paper (Theorem 10) it is shown that also family of everywhere discontinuous functions, that have finitely many values, is 2 c -algebrable.…”
Section: Lemma 13 Let F Be a śWiątkowski Function And X ∈ R Be A Darmentioning
confidence: 93%
“…A special case of this theorem was proved in [4]. The proof of this theorem uses the Fichtenholz-Kantorovitch-Hausdorff Theorem, which in turn, can be considered as a special case of Theorem 1.1.…”
Section: Introductionmentioning
confidence: 97%